Impact of Industry 4.0 on Occupations and Employment in Turkey - Sumer, Beyza (European Scientific Journal, ESJ, 2018)
New technologies of this age is widely referred as Industry 4.0. The rapid increase in digitalization, robotization, and intelligent automation has great impact on markets, including the labour market. Technological changes destroy some jobs while generating new jobs and occupations. Replacement of jobs by robots, smart vehicles, digitalized and connected processes will have great impact on labour market resulting in mass unemployment. This paper aims to highlight prospective changes in occupations and job losses due to new technologies in Turkey. Following the introduction part, the paper proceeds to literature review about the effect of new technologies on jobs, skills, tasks, occupations, and employment. In the next part, a time analysis of occupations in Turkey takes place in order to bring out the occupations which might be substituted by Industry 4.0, and thus might result in mass unemployment. A framework for susbstitutable and complementable occupations in Turkey has been constituted in this part, too. In the concluding remarks, it has been put forward that there will be considerable losses in some occupational categories with routine tasks, both in manual and cognitive jobs. In some other jobs, new technologies have a complementing effect which might lead to employment generation. It has been suggested that Turkey can get the better of negative impacts of Industry 4.0 by fully analysing the issue, improving training and skills upgrading, and promoting jobs in technology and creativity related new fields such as cultural and creative industries.